2014
DOI: 10.1016/j.bmc.2014.01.052
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic cardiac glycosides and coumarins from Antiaris toxicaria

Abstract: Eight new cardiac glycosides/aglycones (antiaritoxiosides A–G, 1–7, and antiarotoxinin B, 8), two new coumarins (anticarins A–B, 41–42), and two new flavanones (antiarones L–K, 43–44) were isolated from trunk bark of Antiaris toxicaria together with 53 known compounds. The new structures were established by extensive analysis of spectroscopic data. Compound 1 (10-carboxy and 3α-hydroxy) and compounds 3–6 (10-hydroxy) contain unique substituents that are rarely found in cardiac glycosides. The cytotoxic effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 42 publications
2
21
0
1
Order By: Relevance
“…Such a retro-Prins-type reaction based mechanism could also be extended to the biosynthesis of other 19-nor cardiac glycosides, as reported from Antiaris toxicaria recently. 36 …”
Section: Resultsmentioning
confidence: 99%
“…Such a retro-Prins-type reaction based mechanism could also be extended to the biosynthesis of other 19-nor cardiac glycosides, as reported from Antiaris toxicaria recently. 36 …”
Section: Resultsmentioning
confidence: 99%
“…The other nine known compounds were identified as xanthyletin (4) (Hong et al, 2012), seselin (5) (Hong et al, 2012), umbelliferone (6) (Olennikov et al, 2012), 7-demethylsuberosine (7) (Kang et al, 2001), 8-hydroxy-7-methoxy-6-prenylcoumarin (8) (Filho et al, 1972), vaginol (9) (Zou et al, 2005), antiarsin B (10) (Jiang et al, 2009), antiarone K (11) (Shi et al, 2014), and antiarone F (12) (Hano et al, 1990a) by comparison of their physical and spectroscopic properties with those reported in the literatures.…”
Section: Nomentioning
confidence: 99%
“…Previous chemical investigations of this species have revealed that it was rich in cardiac glycosides, especially from its latex Que et al, 2010) and seed (Zuo et al, 2013). Apart from the cardiac glycosides, prenylflavanones (Hano et al, 1990a,b;Hano et al, 1991;Que et al, 2009), phenylpropanoid and lignan derivatives (Jiang et al, 2009), and coumarin derivatives (Shi et al, 2014) were other kinds of components discovered from this plant, which exhibited anti-osteoporosis (Jiang et al, 2009) and antibacterial activities (Que et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The active components are cardenolides and alkaloids, which include cardiac glycoside, coumarins, and flavanones. 38 The most important toxin is a cardiac glycoside named antiarin. Clinical manifestations are similar to digitalis overdose and the management is supportive.…”
Section: Treatmentmentioning
confidence: 99%